Implementation of Digitalization of City Infrastructure for Improved Sustainability: Case Study on Smart City Project in Surabaya, Indonesia - Judijanto, Loso; Erkamim, Moh.; Dolphina, Erlin; Utama, I Wayan Karang (West Science Nature and Technology, 2023)
The application of digitalization in urban contexts, particularly through Smart City initiatives, has become an important avenue to address the complexities of modern urban life. This study focuses on the Smart City Project in Surabaya, Indonesia, aiming to quantitatively analyze the impact of digitalization on sustainability indicators from a community perspective. A quantitative approach, including a survey of 190 residents and regression analysis, was used to comprehensively explore the relationship between demographic factors, perceptions of digital infrastructure and sustainability outcomes. The results showed statistically significant improvements in sustainability indicators, with waste reduction behavior and community satisfaction being particularly important. Regression analysis shows that age, income, and digital literacy significantly influence sustainability outcomes. These findings contribute to the growing body of knowledge on Smart Cities initiatives, offering insights for policymakers, urban planners, and community leaders to increase the effectiveness of digitalization in fostering sustainable urban environments.